A Generation of Revolutionaries : Nikolai Charushin and Russian Populism from the Great Reforms to Perestroika - Eklof, Ben, 1946-; Saburova, T. A. (Tatʹi︠a︡na Anatolʹevna) (Book collections on Project MUSE., 2017)
"Nikolai Charushin's memoirs of his experience as a member of the revolutionary populist movement in Russia are familiar to historians, but A Generation of Revolutionaries provides a broader and more engaging look at the lives and relationships beyond these memoirs. It shows how, after years of incarceration, Charushin and friends thrived in Siberian exile, raising children and contributing to science and culture there. While Charushin's memoirs end with his return to European Russia, this sweeping biography follows this group as they engaged in Russia's fin de siecle society, took part in the 1917 revolution, and struggled in its aftermath. A Generation of Revolutionaries provides vibrant and deeply personal insights into the turbulent history of Russia from the Great Reforms to the era of Stalinism and beyond. In doing so, it tells the story of a remarkable circle of friends whose lives balanced love, family and career with exile, imprisonment, and revolution."--Provided by the publisher